Screening of lignin degrader from soil - Yeoh, Teik Loon (2006)
Lignin creates the main problem in waste from the pulp and paper industry. The pulp and paper industry is always interested in finding new, cheaper and more effective ways of get lignin out so that they can get to the cellulose fibres. Lignin degrading bacteria and enzyme is characterized. Important aspects of the production of the enzyme by lignin degrading bacteria studied include the characterization of enzyme and improvement of yield. This process includes a two phases: screening process and the characterization process. Screening process was done using selective agar containing alkaline lignin. The microbe was characterized using gram staining, spore staining and acid-fast staining. The lignin degrading microbe found was tested; the result was a gramnegative bacteria, has no endospore and is not acid fast. The optimum pH found was 6.0 while the optimum temperature examined was 40°C and gave the maximum enzyme activity of 2.00E-05μmol/ml/min. The effect of carbon source and nitrogen source on the enzyme production was also studied. Carbon sources that were compared were carboxy methyl cellulose, glucose and xylose. It was proven that xylose is the best carbon source among the three. While nitrogen sources compared were yeast extract, peptone and urea. The best nitrogen source among the three was yeast extract and peptone.